Penerapan Desentralisasi Pendidikan pada Manajemen Berbasis Sekolah dari Pola Lama (Sebelum Desentralisasi Pendidikan) ke Pola Baru (Era Desentralisasi) - Indra Saputra; Firman Firman; Riska Ahmad (Keguruan, 2022)
The era of educational decentralization has brought fundamental changes in various lives, including educational life. With decentralization, schools will be free to manage resources and sources of funds by allocating them according to priority needs, as well as being more responsive to local needs. Teacher activity and creativity can be realized if a school work climate is created that is conducive and appropriate to the objectives of the activity. The Education Office (including supervisors) does not interfere in the management of learning which is the full responsibility of the school principal. Schools belong to the local community, BP3 and parties who care about the interests of the school. So that students will become subjects not only objects that directly become the focus of the target involved by the teacher in selecting activities.